2002
DOI: 10.2320/matertrans.43.712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Directionally Solidified B<SUB>4</SUB>C-TiB<SUB>2</SUB> Composites Prepared by a Floating Zone Method

Abstract: Directionally solidified B 4 C-TiB 2 composites were prepared by a Floating Zone method. TiB 2 phases in a rod shape were continuously connected in the B 4 C matrix. The c-axes of TiB 2 and B 4 C phases were perpendicular and tilted 22 • to the growth direction, respectively. The (101) and (120) planes of the B 4 C were in parallel to the (001) and (100) planes of TiB 2 , respectively. The electrical conductivity of the composite parallel to the growth direction (σ ) was greater than monolithic B 4 C by a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 19 publications
4
50
1
Order By: Relevance
“…We have reported the rod-shape texture in the B 4 C-TiB 2 eutectic composite, where the TiB 2 phase was 20 vol%. 14) The spacing between lamellae decreased with increasing the growth rate. The time for the diffusion of solutes around the solid/liquid interface should be short at a high growth rate.…”
Section: The Study Of the Eutectic Structurementioning
confidence: 99%
“…We have reported the rod-shape texture in the B 4 C-TiB 2 eutectic composite, where the TiB 2 phase was 20 vol%. 14) The spacing between lamellae decreased with increasing the growth rate. The time for the diffusion of solutes around the solid/liquid interface should be short at a high growth rate.…”
Section: The Study Of the Eutectic Structurementioning
confidence: 99%
“…Some promising results have been reported for the B 4 C-SiC, B 4 C-TiB 2 and B 4 CTiB 2 -SiC eutectic composites. [18][19][20] However, the study on the TiC-TiB 2 -SiC eutectic composite has not been reported. In this study, the TiC-TiB 2 -SiC ternary composites were prepared by arc-melting, and the microstructure, hardness, thermal conductivity and electrical conductivity were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] We have prepared B 4 C-SiC eutectic composites by a floating zone (FZ) method, and reported significantly higher oxidation resistance than that of B 4 C. 13) Titanium diboride (TiB 2 ) can be a useful additive material to improve the performance of B 4 C because of its high electrical conductivity, thermal conductivity and hardness. [14][15][16][17][18][19][20] We have reported the characteristics and microstructure of B 4 C-TiB 2 eutectic composites. 18,21) Since the fracture toughness of B 4 C will be improved by addition of TiB 2 , the B 4 C-TiB 2 eutectic composite could be a candidate engineering material.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] We have reported the characteristics and microstructure of B 4 C-TiB 2 eutectic composites. 18,21) Since the fracture toughness of B 4 C will be improved by addition of TiB 2 , the B 4 C-TiB 2 eutectic composite could be a candidate engineering material. Therefore, B 4 C-TiB 2 -SiC can be a potential structural material with several excellent combined properties of B 4 C-TiB 2 and B 4 C-SiC composites such as good ductility and oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%